2015
DOI: 10.1001/jamaneurol.2014.3958
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds and Early Recurrent Stroke After Transient Ischemic Attack

Abstract: The risk of early recurrent stroke after transient ischemic attack (TIA) may be modifiable by optimal treatment. Although ABCD 2 scores, diffusion-weighted imaging lesions, and large artery stenosis are well known to predict early stroke recurrence, other neuroimaging parameters, such as cerebral microbleeds (CMBs), have not been well explored in patients with TIA. OBJECTIVE To determine the rate of early recurrent stroke after TIA and its neuroimaging predictors. DESIGN, SETTING, AND PARTICIPANTS In this hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
(9 reference statements)
1
31
0
Order By: Relevance
“…Previous studies showed that certain CSVDs such as HWHs, CMBs, and ALIs were independent predictors for a poor outcome after index stroke2122 or the long-term fatal outcome 11232425. However, there has been no information on the impact of the total burden of CSVDs on clinical outcomes despite various types of CSVDs commonly coexisting and the clinical outcome possibly being determined by their combined effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that certain CSVDs such as HWHs, CMBs, and ALIs were independent predictors for a poor outcome after index stroke2122 or the long-term fatal outcome 11232425. However, there has been no information on the impact of the total burden of CSVDs on clinical outcomes despite various types of CSVDs commonly coexisting and the clinical outcome possibly being determined by their combined effect.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with SVD, diffuse hypoperfusion and long-standing hypertension, which commonly leads to lipohyalinosis, are most well-known causes of it. [16, 17] In this condition, cerebral auto-regulation and compensatory collateral blood flow are impaired. [18, 19] Thus, a minor ischemic insult could cause symptomatic stroke events.…”
Section: Discussionmentioning
confidence: 99%
“…11–13 The presence of CMBs is considered a strong predictor of future stroke, particularly haemorrhagic stroke 1415 There is evidence that large artery atherosclerosis may be associated with CMBs, but the results are controversial.…”
Section: Introductionmentioning
confidence: 99%